INTEGRASI REMEDIASI MISKONSEPSI SISWA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN FLUIDA STATIS DI SMA - Wahyuni, Sri; Djudin, Tomo; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this research was determined the effect of integrated remediation misconception in fluid static learning use model problem based learning to changing student misconception in grade XI SMA Negeri 1 Sungai Raya. The research used pre-experimental design with one group pretest-posttest design involving 24 students of class XI IPA 3 as a sample which selected by intact group. Diagnostic test which consist of 18 multiple choice question with open reasoning was used as research instrument to asses the number of students misconception. Based on the result, the average percentage decrease of misconception students for each students equal to 74,50%. Based on an analysis using price obtained McNemar test, Ï‡2count (252,03) ËƒÏ‡2table (3,84) for df = 1 and Î± = 5% indicate the conception significant changes between before and after integrated remediation misconception in fluid static learning use model problem based learning. The effectiveness of integrated remediation misconception in fluid static learning use model problem based learning of DQM (The Decreasing of Quantity of the student that Misconception) equal to 74,63% in high category.Keywords: integrated remediation, misconception, model problem based learning, fluid static